THE TRANSFORMATION OF ISLAMIC CIVILIZATION: A HISTORICAL ANALYSIS OF THE CLASSICAL PERIOD AND THE GOLDEN AGE - Yugo, Tri Yugo; Saepudin, Aep (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2024)
This research examines the transformation of Islamic civilization from the classical period to the golden age, focusing on contributions to science, culture, and politics. This period, which lasted from the 7th to the 13th century, was the pinnacle of Islamic civilization's glory with achievements in mathematics, medicine, astronomy, and philosophy. The research method used is descriptive-qualitative with historical analysis, supported by primary literature such as books and scientific journals. The results of the study show that during this period, Islamic civilization was able to absorb and develop knowledge from Greece, Persia, and India, through institutions such as Baitul Hikmah in Baghdad. The contributions of Muslim scientists such as Al-Khawarizmi and Ibn Sina had a long-term impact on the development of modern science in Europe through translation into Latin. In conclusion, the transformation of Islamic civilization in the Golden Age significantly built the foundation of global science and triggered an intellectual awakening in Europe during the Renaissance period